MicroRNAs and lipoproteins: A connection beyond atherosclerosis? - Norata, Giuseppe; Sala, F.; Catapano, A.; Fernández-Hernando, C. (Elsevier Ireland, 2013)
MicroRNAs (miRNAs) are short non-coding RNAs involved in the regulation of gene expression at the post-transcriptional level that have been involved in the pathogenesis of a number of cardiovascular diseases. Several miRNAs have been described to finely regulate lipid metabolism and the progression and regression of atherosclerosis including, miR-33, miR-122. Of note miR-33a and -33b, represent one of the most interesting and attractive targets for metabolic-related disorders and anti-miR-33 approaches are under intensive investigation.More recently miRNAs were shown to exert their activities in a paracrine manner and also systemically. The latter is possible because lipid-carriers, including lipoproteins, transport and protect miRNAs from degradation in the circulation.This review will present the complex mechanism by which miRNAs regulate lipid metabolism, illustrate how their therapeutical modulation may lead to new treatments for cardiometabolic diseases, and discuss how lipoproteins and other lipid-carriers transport miRNAs in the circulation.The emerging strong connection between miRNAs, lipoproteins and lipid metabolism indicates the existence of a reciprocal modulation that might go beyond atherosclerosis. © 2012 Elsevier Ireland Ltd.